Endothelial G protein stimulatory α-subunit is a critical regulator of post-ischemic angiogenesis - He, Lifan; Lu, Hanlin; Chu, Jianying; Qin, Xiaoteng; Gao, Jiangang; Chen, Min; Weinstein, Lee S.; Yang, Jianmin; Zhang, Qunye; Zhang, Cheng; Zhang, Wencheng (Frontiers in Cardiovascular Medicine, 2022)
Post-ischemic angiogenesis is a vital pathophysiological process in diseases such as peripheral arterial disease (PAD), heart ischemia, and diabetic retinopathy. The molecular mechanisms of post-ischemic angiogenesis are complicated and not fully elucidated. The G protein stimulatory alpha subunit (Gsα) is essential for hormone-stimulated cyclic adenosine monophosphate (cAMP) production and is an important regulator for many physiological processes. In the present study, we investigated the role of endothelial Gsα in post-ischemic angiogenesis by generating adult mice with endothelial-specific Gsα deficiency (GsαECKO). GsαECKO mice had impaired blood flow recovery after hind limb ischemic injury, and reduced neovascularization in allograft transplanted tumors. Mechanically, Gsα could regulate the expression of angiogenic factor with G patch and FHA domains 1 (AGGF1) through cAMP/CREB pathway. AGGF1 plays a key role in angiogenesis and regulates endothelial cell proliferation as well as migration. Knockdown of CREB or mutation of the CRE site on the AGGF1 promoter led to reduced AGGF1 promoter activity. In addition, knockdown of AGGF1 reduced the proangiogenic effect of Gsα in endothelial cells, and overexpression of AGGF1 reversed the impaired angiogenesis in GsαECKO mice in vivo. The finding may prove useful in designing new therapeutic targets for treatments of post-ischemic angiogenesis-related diseases.